Pengaruh Model Pembelajaran Problem Posing Tipe Pre-Solution Posing terhadap Hasil Belajar IPA di SMP Muhammadiyah 3 Jakarta - Miftahul Jannah (Navigation Physics : Journal of Physics Education, 2022)
This study aims to determine the influence of the Pre-Solution Posing type Problem Posing learning model on the science learning outcomes of students of SMP Muhammadiyah 3 Jakarta. This study uses a quasi-experimental method, the affordable population comes from class IX consisting of four classes. From the affordable population, two samples of classes were taken, of which one class as an experimental class and the other class as a control class. Class IX-A was selected as the experimental class and class IX-B as the control class. Data obtained from formative tests on the subject of dynamic electricity, then analyzed statistically to find out whether there is a difference in the value of science learning outcomes between the experiment class (students who are taught with the Pre-Solution Posing type Problem Posing learning model) and the dick class (students who are not taught with the Pre-Solution Posing type Problem Posing model or with expository learning strategies). The results showed that the application of the Pre-Solution Posing type Problem Posing model can improve student science learning outcomes, where the increase in student science learning outcomes is 12.76%.